Ministry of Trade and Industry Decree No. 465 of the Year 2013 In Respect of Cancelling the Export Duty Imposed on Some Feedstuff Items = وزراة التجارة والصناعة قرار رقم 465 لسنة 2013 فى شأن إلغاء رسم الصادر على بعض أصناف مكونات الأعلاف - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.